The Avocado: Botany, Production and Uses 2002
DOI: 10.1079/9780851993577.0101
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology.

Abstract: Many factors may be responsible for the low average avocado yield in most countries, and for the wide fluctuations in yield from year to year. Low yield in healthy trees, which are not subjected to water or nutritional stresses, occur mainly as a result of inadequate fruit set, or excessive fruit drop. This chapter discusses the successive stages of fruit formation in relation to initial and final fruit set.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…Subtropical avocados cultivars, that are developed with success in the tropics at high altitudes and in the subtropics with cold winters, can produce floral buds only if they are kept under regimes of cold temperatures (Gazit and Degani, 2002), a requirement that is not, however, essential to the cultivars of avocados that grow in cold climates, in semi-arid and tropical and semi-tropical climates. …”
Section: Vegetative Development Of Avocadomentioning
confidence: 99%
See 4 more Smart Citations
“…Subtropical avocados cultivars, that are developed with success in the tropics at high altitudes and in the subtropics with cold winters, can produce floral buds only if they are kept under regimes of cold temperatures (Gazit and Degani, 2002), a requirement that is not, however, essential to the cultivars of avocados that grow in cold climates, in semi-arid and tropical and semi-tropical climates. …”
Section: Vegetative Development Of Avocadomentioning
confidence: 99%
“…Romero (2011) found that in a year of high production, more than 100x10 3 flowers produced only 168 became a fruit. In other cases, such as adult trees Guatemalan race, fruit set barely reached between 0.001% and 0.23% of a total of more than 1.5 x 10 6 flowers (Gazit and Degani, 2002), and Lahav and Zamet (1999) indicates, for the cultivar Fuerte, that only 0.015% of flowers become ripe fruits. In short, the avocado is a species with very intense flowering in subtropical conditions where it may exceed 2 x 10 6 flowers of which only between 0.001% and 0.1% reach the fruit set (Salazar-García and Lovatt, 1998;Dixon and Sher, 2002;Can-Alonzo et al, 2005;Cossio-Vargas et al, 2007b, Garner andLovatt, 2008).…”
Section: Fertilizationmentioning
confidence: 99%
See 3 more Smart Citations